2009
DOI: 10.1016/j.marenvres.2008.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Dietary cadmium and benzo(a)pyrene increased intestinal metallothionein expression in the fish Fundulus heteroclitus

Abstract: Fish were individually fed food pellets containing cadmium, benzo(a)pyrene, or a combination of the two, then analyzed for metallothionein mRNA expression in the intestine, liver, and gill using real-time RT-qPCR. An initial experiment using only cadmium showed that ingestion of pellets varied in individual fish, and estimates of cadmium dose from the numbers of ingested pellets indicated considerable individual variability in cadmium dose. Induction of intestinal metallothionein mRNA was apparent, however, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Moreover, they evaluated developmental deformities by “visual inspection” at 36 hpf at which time point development (organogenesis) is still occurring. Other effects of dietary BaP exposures to fish have been investigated (Couillard et al, 2009; Roesijadi et al, 2009; Yuen and Au, 2006), but none of these studies investigated offspring development or multigenerational effects.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they evaluated developmental deformities by “visual inspection” at 36 hpf at which time point development (organogenesis) is still occurring. Other effects of dietary BaP exposures to fish have been investigated (Couillard et al, 2009; Roesijadi et al, 2009; Yuen and Au, 2006), but none of these studies investigated offspring development or multigenerational effects.…”
Section: Discussionmentioning
confidence: 99%
“…Such increase in MT mRNA levels after Cd exposure was observed in Crassostrea virginica (Unger and Roesijadi 1993), M. galloprovincialis (Dondero et al 2005), and C. edule (Paul-Pont et al 2010). Several recent studies were interested to the MT mRNA expression as a biomarker of metal pollution instead of the MT/MTLP quantification in bivalves (Unger and Roesijadi 1993;Lemoine et al 2000;Lemoine and Laulier 2003;Dondero et al 2005;Banni et al 2007;LadharChaabouni et al 2008;Choi et al 2008;Bigot et al 2009), fishes (Tom et al 2004;Kim et al 2008;Gao et al 2009;Roesijadi et al 2009), crab (Gao et al 2011) etc., and showed an increase of MT mRNA levels after exposure to metals. Nevertheless, Chang et al (2007) showed a decrease of MT mRNA levels in gills of the clam Meretrix lusoria exposed to 200 and 1,000 μg/l of Cd during 5 days.…”
Section: Mt Induction and Physiological Variabilitymentioning
confidence: 99%
“…The majority of contaminants rarely occur as single compounds, and are most commonly present in the form of mixtures containing chemicals that either do not interact or mutually interact to exert joint actions. Thus, studies of their combined effect have become increasingly important for predicting toxic impact of contaminants on marine organisms (Maria and Bebianno, 2011;Ragusa et al, 2017;Roesijadi et al, 2009). Of all the major contaminants of coastal ecosystems, metals have received significant attention given their ubiquitous distribution and long term persistence in the sediment and biota.…”
Section: Introductionmentioning
confidence: 99%